Key technology and standardization progress for 5G - Qingyang WANG; Peirong XIE; Shangkun XIONG; Yao WEI; Yu LIU; Wenyi LI; Jinlian WU (Dianxin kexue, 2017)
Under the impetus of the global industry,the 5G technology developes rapidly and has entered the critical stage of standard setting and technical verification.Based on this,the key technologies of 5G and its latest standardization progress was introduced mainly,including massive MIMO,new radio network architecture,ultra dense network,edge computing,network slicing,networking on-demand ,4G and 5G interworking,as well as industry organization and operator dynamics,and ended with some thoughts and suggestions.